Pengaruh Konseling Kelompok terhadap Perkembangan Keterampilan Sosial Siswa Sekolah Dasar Negeri 60 Kota Bengkulu - Hasanah, Elya; Putri, Astri Maisa; Ganarsih, Inggit; Delia, Lola; Azzahra, Anggun; Zubaidah, Zubaidah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Given the significance of social skills in classroom interactions and the school environment, this research aims to investigate the impact of group counseling on the social skill development of primary school students. Students with this ability can effectively communicate their feelings and fit in with others. The State Elementary School 60 in Bengkulu City was seen to have deficient social skills, as evidenced by the children’s disorganized behavior, lack of empathy, and frequent confrontations. Descriptive qualitative approaches including observation, interviews, and questionnaires are used in this study. The findings indicate that group counseling improves students’self-esteem, self-control, and understanding of individual differences. The success of this program is largely due to the role that teachers and counselors play in setting a positive example, as well as the support of other instructors and school principals. Infrastructure and a variety of tactics can be used to get around constraints like time and resource limitations. Establishing an environment that fosters children’s social skills also requires parental assistance. All things considered, group therapy has shown to be successful in enhancing students’ social skills as a corrective and preventive measure, enhancing the standard of instruction and the personal growth of students.